Serum adipokines and adipose tissue distribution in rheumatoid arthritis and ankylosing spondylitis. A comparative study. - TOUSSIROT, ERIC; Grandclement, Emilie; Gaugler, Beatrice; Michel, Fabrice; Wendling, daniel; Saas, Philippe; Dumoulin, Gilles; bt, cic (Frontiers in Immunology, 2013)
Rheumatoid arthritis (RA) and ankylosing spondylitis (AS) are inflammatory rheumatic diseases that may modify body composition. Adipose tissue has the ability to release a wide range of products involved in physiologic functions, but also in various pathological processes, including the inflammatory/immune response. RA and AS are both associated with the development of cardiovascular complications. It is has been established that central/abdominal and particularly intra-abdominal or visceral adiposity is closely linked to cardiovascular events. Thus, in this study, we aimed to evaluate the body composition of patients with RA or AS compared to healthy controls (HC) with a special emphasis on the visceral region. In parallel, we measured adipose products or adipokines, namely leptin, adiponectin and its high molecular weight (HMW) isoform, resistin, and ghrelin, a gastric peptide that plays a role in energetic balance. The homeostasis model assessment for insulin resistance (HOMA-IR) and atherogenic index were used to evaluate cardiovascular risk. One hundred and twelve subjects were enrolled (30 patients with RA, 31 with AS and 51 HC). Body composition was measured using dual-energy X-ray absorptiometry (DXA) to determine total fat mass and lean mass, adiposity, fat in the android and gynoid regions, and visceral fat. Patients and HC did not differ in terms of body mass index. On the contrary, adiposity was increased in RA (p= 0.01) while visceral fat was also increased, but only in women (p=0.01). Patients with AS tended to have lower total fat mass (p=0.07) and higher lean mass compared to HC (p = 0.07). Leptin and leptin/fat mass were decreased in male patients with AS (p